Infeksi Parasit Usus pada Penduduk di Sekitar Tempat Pembuangan Akhir Sumompo Kota Manado - Winerungan, Claudia C.; Sorisi, Angle M. H.; Wahongan, Greta J. P. (UNIVERSITAS SAM RATULANGI, 2020)
Abstract: Intestinal parasitic disease is one of the most common health problems in the world. The high prevalence of intestinal parasites in Indonesia is supported by the geographical location of Indonesia as a tropical climate country that has a high humidity level. Wastes being piled up at the landfill has the potential to cause pollution to the surrounding environment which can be a source of infection of intestinal parasites. This study was aimed to find out the profile of intestinal parasitic infections among the population around Sumompo landfill at Manado. This was a descriptive survey conducted from September to November 2019. Respondents were residents of Sumompo District who lived around the Sumompo landfill. There were 100 residents that returned the containers containing feces samples, which were then examined at the Laboratory of Parasitology Faculty of Medicine Sam Ratulangi University. The results showed that only 6 out of 100 samples (6%) contained intestinal parasites which was a type of intestinal protozoa namely Blastocystis hominis. In conlcusion, 6 out of 100 residents around Sumompo landfill at Manado were infected with Blastocystis hominis.Keywords: intestinal parasites, landfillÂ Abstrak: Penyakit parasit usus merupakan salah satu masalah kesehatan terbanyak di dunia. Prevalensi parasit usus di Indonesia tergolong tinggi didukung oleh letak geografis Indonesia sebagai negara beriklim tropis yang memiliki tingkat kelembaban tinggi. Sampah kota yang ditimbun di tempat pembuangan akhir (TPA) berpotensi menyebabkan pencemaran terhadap lingkungan disekitarnya yang dapat menjadi sumber infeksi dari parasit usus. Penelitian ini bertujuan untuk mengetahui gambaran prevalensi infeksi parasit usus pada penduduk di sekitar TPA Sumompo Kota Manado. Jenis penelitian ialah survei deskriptif dilakukan pada bulan September sampai dengan November 2019. Subjek penelitian ialah penduduk Kelurahan Sumompo yang tinggal di sekitar TPA Sumompo Kota Manado. Hasil penelitian mendapatkan 100 penduduk mengembalikan pot sampel berisi tinja, kemudian diperiksa di Laboratorium Parasitologi FK Unsrat. Didapatkan 6 dari 100 sampel (6%) yang mengandung parasit usus yaitu sejenis protozoa usus Blastocystis hominis. Simpulan penelitian ini ialah 6 dari 100 penduduk di sekitar TPA Sumompo Kota Manado terinfeksi parasit usus, yaitu Blastocystis hominis.Kata kunci: parasit usus, tempat pembuangan akhir